The The Influence of Tabe' Culture in Shaping Students Character - Khaerul, Khaerul (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2024)
This research aims to determine: How is the understanding of tabe' culture among students at SMAN 4 Pinrang? How is the implementation of tabe' culture at SMAN 4 Pinrang? What is the influence of tabe' culture in shaping the character of students at SMAN 4 Pinrang? The approach used in this research is quantitative approach. The data collection techniques used are questionnaires or surveys, observation, and documentation. The data analysis used in this research is simple linear regression analysis. From the data obtained, it can be said that the understanding and implementation of tabe' culture at SMAN 4 Pinrang fall into the moderate category with a percentage of 58.33%. Meanwhile, the students' character at SMAN 4 Pinrang also falls into the moderate category with a percentage of 66.66%. Furthermore, it is found that there is an influence of tabe' culture in shaping the character of students at SMAN 4 Pinrang. This is supported by the partial testing results (t-test) which yielded a value of ????ℎi????????????g > ????????????????????????, that is, 5.218 > 1.691. The results of simple linear regression analysis indicate that if tabe' culture (X) increases by 1 point, the character of students (Y) will increase by 0.914 with a constant of 5.690. In other words, the better the tabe' culture, the better the character of the students will be